UMP lecturers assist in design of air pollution control modular system for clinical waste incineration - Mohamad Rizza, Othman (2022)
PAYA BESAR, 14 June 2022 - Since the World Health Organization (WHO) announced COVID-19 as a pandemic in March 2020, the outbreak has been spreading rapidly around the world.